Advance Synthetic Approaches to 1,2,3-triazole Derived Compounds: State of the Art 2004-2020 - Sahu, Adarsh (Current Organocatalysis, 2021)
Background: 1,2,3-triazole is considered a widely explored scaffold by medicinal chemists because of its therapeutic importance. The structural characteristics of 1,2,3-triazoles allow it to mimic certain functional groups demonstrating its utility to prepare new medicinal compounds using the concept of bioisosterism and molecular hybridization. Centered on Huisgens cycloaddition reaction, over the past decade and a half, developed click chemistry approaches to furnish triazole derivatives with various applications ranging from drugs to bioconjugation linkers. Objective: In the present review, we aim to highlight the different approaches developed for the synthesis of 1,2,3-triazole derivatives and in particular, advances in synthetic methods for the last 16 years. This review is also intended to help researchers for finding potential future directions and scope in the development of synthetic strategies. Conclusion: As summarized through the compilation of recent advances for 1,2,3-triazole synthesis, it is clear that these protocols have numerous advantages such as cleaner reaction profile, shorter reaction times, excellent product yields, environmentally benign milder reactions, and safe operations.
Keywords: solvent-free